Revenue and Incentive Effects of Basis Step-Up at Death: Lessons from the 2010 “Voluntary” Estate Tax Regime - Gordon, Robert; Joulfaian, David; Poterba, James (American Economic Review, 2016)
In 2010, the U.S. estate tax expired and executors of wealthy decedents were not required to file estate tax returns. In the absence of the estate tax, beneficiaries received assets with carryover rather than stepped-up basis. Unrealized capital gains accounted for 44 percent of the fair market value of non-cash assets in estates that chose the carryover basis regime, and an even higher percentage for some asset categories. Many of the largest gains were on assets that had been held for at least two decades.